ANALYSIS OF TRANSLATION SHIFT IN BILINGUAL CHILDREN'S STORYBOOKS - Tri Widarwati, Nunun; Purnomo, Budi; Indri Astuti, Purwani; Wijayava, Ratih (English Review: Journal of English Education, 2024)
lingual illustrated children's stories are excellent tools for teaching English to beginners, particularly children. Translating such stories requires the use of simple and easily understandable language to aid children's growth and development. Thus, it is crucial that translation shifts in children's stories effectively convey meaning and are suitable for young learners. This study focuses on the translation shifts in the illustrated bilingual children's story "The Mouse and the Frog," which is rich in moral values and character development.The urgency of this research lies in identifying and analyzing the types and forms of translation shifts in noun phrases within the story. The objective is to develop models and provide empirical evidence on these shifts, enhancing understanding of translation practices, particularly in the context of noun phrases. The research employs document analysis and data triangulation methods, with media sourced from a YouTube channel.Results indicate that translation shifts in noun phrases predominantly occur in the form of unit shifts. This study aims to contribute a new model to the field of English translation, improving and expanding knowledge in this area. The findings are expected to enhance readers' understanding of translation, particularly for beginners in English, and provide insights for translators working with children's literature.